A review of the importance on the need of micro medical and health takaful - Fauzilah, Salleh; Nahidah, Mustafa; Ahmad Shukri, Yazid; Puspa Liza, Ghazali; Wan Norhayate, Wan Daud; Norizan, Remli; Burhan, N.A.S (2017)
The overall aim of this thesis is to discuss health care expenses incurred and borne by the government as well as the citizens. The issues and challenges raised in regard to the implementation of Health Takaful in Malaysia has been thoroughly assessed by focusing on low to moderate level individuals, specifically the hard-core poor, poor and low (B40), and moderate-income earners (M40). Moreover, the development of Medical and Health Insurance (MHI) / Medical and Health Takaful (MHT) in Malaysia has also been reviewed accordingly in this study. Therefore, it is very important for future studies to work on the framework development of micro health Takaful.